Dual Wide-Band Polarization Insensitive Metamaterial Absorber Based on Concentric Split-Ring and Circular Ring Resonators - Anshu Arya; Dr. Sandeep Kumar Prasad (Revista Electronica de Veterinaria, 2024)
This paper presents a novel dual wide-band polarization insensitive metamaterial absorber design incorporating concentric split-ring resonators (CSRRs) and circular ring resonators (CRRs). The proposed structure demonstrates exceptional absorption performance across two distinct frequency bands while maintaining polarization independence and wide-angle stability. Through comprehensive electromagnetic simulations and equivalent circuit modeling, we achieve absorption rates exceeding 90% in both operational bands. The design exhibits robust performance for oblique incidence angles up to 60° and maintains consistent absorption characteristics regardless of polarization orientation. The metamaterial unit cell comprises a three-layer configuration with optimized geometric parameters to ensure dual-band operation. This work contributes significantly to the advancement of metamaterial absorbers for applications in electromagnetic interference shielding, radar cross-section reduction, and sensing technologies.